Angela Borgia - Meyer, Conrad Ferdinand, 1825-1898 (Salt Lake City, UT : Project Gutenberg, 2004)
"Angela Borgia" by Conrad Ferdinand Meyer is a historical novel written during the late 19th century. The narrative centers around the complex character of Lukrezia Borgia, a young woman navigating her tumultuous past while assuming the role of a duchess in Ferrara. The book explores themes of power, identity, and moral ambiguity against the backdrop of the infamous Borgia family's reputation and political intrigues. At the start of the novel, readers are introduced to Lukrezia as she triumphantly enters Ferrara with her new husband, Don Alfonso, the heir of the Duke. As she rides under a grand canopy, the professors of the university accompany her, each pondering the contradictions of her existence$1 (Bone reflecting on her innocence, another on her dark lineage filled with treachery and betrayal. Meanwhile, Angela Borgia, her relative and lady-in-waiting, observes the spectacle, grappling with the shadows of their shared past. This opening portion sets the stage for the intricate relationships and potential conflicts that will unfold, as Angela becomes a witness to the interplay of ambition, loyalty, and betrayal that defines the Borgia legacy. (This is an automatically generated summary.)s
Release date is 2004-09-01
This etext was produced by Michalina Makowska and Michael Pullen
Keywords: Italy -- History -- 1492-1559 -- Fiction